325 degrees C thermoluminescence peak growth in quartz related to oxygen vacancies - Watanabe, S.; Sunta, C. M.; Gamarra, L. Z.; Matsuoka, M.; Yukimitu, K. [UNESP] (Gordon Breach Sci Publ Ltd, 1998)
The thermoluminescence intensity as a function of gamma-ray dose of the 325 degreesC peak, in quartz grains extracted from sea sediments and from fluvial aeolic dunes, is studied. It is found that the response curve at low doses has a concavity directed opposite to that of quartz grains extracted from archaeological potteries. To explain this behavior a model is proposed here based on oxygen vacancies and [AlO4/h](0) centers. The experimentally observed ESR intensity of E-I'-centers as a function of radiation dose can also be explained by this model.
Keywords: Gamma irradiation; Oxygen; Quartz; Sediments; Thermoluminescence; Vacancies